2015
DOI: 10.3390/toxins7041005
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Organ Vasculature in Rat Renal Analysis for Ochratoxin A: Relevance to Toxicology of Nephrotoxins

Abstract: Assumptions surrounding the kidney as a target for accumulation of ochratoxin A (OTA) are addressed because the contribution of the toxin in blood seems invariably to have been ignored. Adult rats were maintained for several weeks on toxin-contaminated feed. Using standard perfusion techniques, animals were anaesthetised, a blood sample was taken, one kidney was ligated, and the other kidney perfused with physiological saline in situ under normal blood pressure. Comparative analysis of OTA in pairs of kidneys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
(42 reference statements)
2
10
0
Order By: Relevance
“…These results indicated that the mice in the OTA group had been poisoned. This deduction was confirmed using H&E staining, electron microscopy, and TUNEL staining, which were consistent with previous reports [40,41]. In addition, we found non-significant variations in CRE levels across all the groups…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results indicated that the mice in the OTA group had been poisoned. This deduction was confirmed using H&E staining, electron microscopy, and TUNEL staining, which were consistent with previous reports [40,41]. In addition, we found non-significant variations in CRE levels across all the groups…”
Section: Discussionsupporting
confidence: 93%
“…These results indicated that the mice in the OTA group had been poisoned. This deduction was confirmed using H&E staining, electron microscopy, and TUNEL staining, which were consistent with previous reports [40,41]. In addition, we found non-significant variations in CRE levels across all the groups due to the fact that OTA mainly affects the renal tubular reabsorption function, but has little effect on glomerular filtration function, and further research is needed to confirm this [42].…”
Section: Discussionsupporting
confidence: 92%
“…Generally, in vitro treatment with relatively high OTA doses provides similar effects to those observed in vivo after chronic low doses exposure, especially in case of DNA-adducts caused by OTA (Pfohl-Leszkowicz and Castegnaro, 2005;Mantle et al, 2015), recent studies carried on human peripheral blood lymphocytes, showed a viability decrease of 20-30% following incubation with OTA concentrations less than 20 μM, (Gonzàlez-Arias et al, 2014;Ali et al, 2011). In the light of these data we have investigated cytotoxicity of OTA on H9 cells with concentrations up to 20 μM, to evaluate the sensibility of and TNF-α (B) mRNA levels were analyzed by real-time PCR using specific primers.…”
Section: Discussionmentioning
confidence: 82%
“…A previous study with albumin-deficient rats showed the very high importance of albumin binding regarding the slow elimination of OTA [ 29 ]. Furthermore, a recent study with rats also proved that the accumulation of OTA in the kidney is due to strong binding of OTA to plasma proteins and its long half-life in plasma [ 255 ]. It is very likely that, in humans, this impact could be more dominant because of the substantially stronger interaction of OTA with human albumin.…”
Section: Displacement Of Ota From Albuminmentioning
confidence: 99%